Articulating structure and agency: how women's studies students express their relationships with feminism. - Bulbeck, Chilla (Women's Studies International Forum)
While “liberal” or “equality” feminism has significant purchase in Australian society, those forms of feminism that identify women's oppression or inequality in terms of structural conditions, be they structures of patriarchy or class, have made less impact at the level of consciousness and policy. The article explores the power of the individualist rhetoric for women's studies students, who, on the whole, reject notions of structural disadvantage in their understanding of feminism and the position of women in society. The students have difficulty articulating the structural constraints that frame women's choices, even after they have spent some months in a women's studies course. The article is based on two sets of original data: a survey of first year women's studies students in 1998, and students' essays in 1999. Copyright (c) 2001 Elsevier Science Ltd